Enhancement programmes conducted by Malaysian Islamic banks towards the implementation of Shariah compliance - Othman, Ahmad Azam; Hassan, Rusni; Arifin, Mahamad; Abdullah, Mohamad Asmadi; Mohd Napiah, Mohammad Deen; Omar, Muhammad Naim (2013)
One of the primary objectives of the Shariah Governance Framework for Islamic Financial Institutions (IFIs) 2010 (SGF 2010) that the Central Bank of Malaysia (Central Bank) has introduced in October 2010 to all IFIs including Islamic banks under the Central Bank jurisdictions is to enhance the role of the Board of Directors (the Board), the Shariah Committee and the management in relation to Shariah matters, including enhancing the relevant key organs having the responsibility to execute the Shariah compliance and research functions aimed at the attainment of a Shariah based operating environment. The Islamic banks need to confirm that they have met all the requirements of the SGF 2010 including to fulfill the abovementioned objective. Thus, this article investigates the enhancement programmes organized and participated by relevant key organs of the Islamic banks. It analyzes the budget allocation for the enhancement programmes, types of enhancement programmes and the enhancement programmes’ target group respectively. This is done through the collection of data and information by distributing the questionnaire to the respondents who involved in Islamic banking industries such as the management of the Islamic banks, Shariah Committee and Shariah officers. Most of the data in this study were collected and analyzed using the Statistical Package for Social Sciences (SPSS) software version 16.0 and Microsoft Excel. Additionally, the descriptive analysis is used to determine the number of frequencies and percentages. The findings and analysis show that the Islamic banks have adopted such objective of the SGF 2010 accordingly and have shown their commitment towards implementing the SGF 2010 requirement. Their commitments are shown in their allocation of certain amount of monies for enhancement programmes for certain targeted groups who are the participants of the programmes.